Turkish Version Study of Parkinson's Disease Quality of Life Questionnaire (PDQL) - KURU ÇOLAK, TUĞBA (AVES, 2015)
Introduction: This study aimed to evaluate Turkish transcultural adaptation, reliability, and validity of Parkinson's Disease Quality of Life Questionnaire (PDQL), which has been developed to assess the quality of life of patients with Parkinson's disease. Methods: Eighty-nine patients who were included in the study were diagnosed with Parkinson's disease. They were presented to the outpatient clinic of the Istanbul Faculty of Medicine, Physical Medicine and Rehabilitation department between July 2005 and April 2008. The Turkish translated version of PDQL (PDQL-TR), Unified Parkinson's Disease Rating Scale (UPDRS), and Hoehn & Yahr (HY) were used as the main outcome measures. Results: The calculated Pearson correlation coefficient for PDQL, H&Y, and UPDRS ranged between -0.36 and -0.80. Cronbach's alpha coefficients of the PDQL-TR complete questionnaire and subdomains were higher than 0.80. The absolute value of item-total score correlation coefficients by Pearson fluctuated between 0.40 (question 4-total score) and 0.88 (question 26-total score), whereas the subdomain-total score correlation coefficients ranged between 0.81 and 0.96. PDQL-TR showed high stability according to the ICC results, ranging between 0.75 (Emotional Function) and 0.88 (Parkinsonian Symptoms). Conclusion: The psychometric features of PDQL-TR are satisfactory, and our results are consistent with the previous literature findings. PDQLTR is a valid and reliable tool to measure health-related quality of life in patients with Parkinson's disease.
Keywords: Parkinson disease; quality of life; reliability; validity; SCALE; RECOMMENDATIONS; INSTRUMENTS; VALIDATION; PDQ-39